Grapevine bZIP transcription factor bZIP45 regulates VvANN1 and confers drought tolerance in Arabidopsis - Niu, Shuaike; Gu, Xiangyang; Zhang, Qian; Tian, Xuemin; Chen, Zhan; Liu, Jingru; Wei, Xiaoju; Yan, Chengxiang; Liu, Ziwen; Wang, Xiaoji; Zhu, Zhengge (Frontiers in Plant Science, 2023)
Drought stress is an important condition that restricts the vegetative growth and reduces the yield of grapevine (Vitis vinifera L.). However, the mechanisms underlying grapevine response and adaptation to drought stress remain unclear. In the present study, we characterized an ANNEXIN gene, VvANN1, which plays a positive role in the drought stress response. The results indicated that VvANN1 was significantly induced by osmotic stress. Expression of VvANN1 in Arabidopsis thaliana enhanced osmotic and drought tolerance through modulating the level of MDA, H2O2, and O2·- at the seedling stage, implying that VvANN1 might be involved in the process of ROS homeostasis under drought or osmotic stress conditions. Moreover, we used yeast one-hybridization and chromatin immunoprecipitation assays to show that VvbZIP45 could regulate VvANN1 expression by directly binding to the promoter region of VvANN1 in response to drought stress. We also generated transgenic Arabidopsis that constitutively expressed the VvbZIP45 gene (35S::VvbZIP45) and further produced VvANN1Pro::GUS/35S::VvbZIP45 Arabidopsis plants via crossing. The genetic analysis results subsequently indicated that VvbZIP45 could enhance GUS expression in vivo under drought stress. Our findings suggest that VvbZIP45 may modulate VvANN1 expression in response to drought stress and reduce the impact of drought on fruit quality and yield.